Bilateral TMJ Ankylosis in a 24-year-old Male with Epilepsy - Elizabeth Floodeen, DDS; Marshall Newman, DMD (Elsevier, 2024)
OBJECTIVES: The purpose of this case report is to outline a unique case of a 24-year-old male with difficult to control seizures and bilateral temporomandibular joint (TMJ) ankylosis including pre-operative workup, the perioperative medical and surgical management, and post-operative course. METHODS: This patient has been followed by the Department of Oral and Maxillofacial Surgery for eight years and eventually developed bilateral TMJ ankylosis, for which bilateral custom joint replacement was recommended. Patient optimization for surgery required a multi-disciplinary approach in conjunction with neurology, anesthesiology, and the ICU/critical care teams. RESULTS: This patient was able to successfully undergo surgery, consisting of bilateral custom TMJ replacement. This case offered a challenge in both peri-operative anti-epileptic management for seizure control as well as airway management with the use of an awake nasal fiberoptic intubation then converted to a tracheostomy. CONCLUSIONS: Bilateral TMJ ankylosis is a rare and often difficult to manage condition. This report provides a unique case of a patient with difficult-to-control seizures and bilateral TMJ ankylosis as well as a discussion of management strategies and recommendations. IMPLICATIONS: There is currently very literature in the OMS field of management recommendations for bilateral TMJ ankylosis and none in patients with a history of epilepsy or seizures. This report will offer the management strategies of these authors.